Research on the Impact of Online Media on Rural Left-behind Children - Wang, Jiaqi (Transactions on Social Science, Education and Humanities Research, 2023)
This article uses the interview method on ten middle school students from Daliangshan, Sichuan, analyzes the negative and positive impact of network media on rural left-behind children, attaches importance to the issues of rural left-behind children using network media, and analyzes the causes of the perspective of children’s psychological cognitive development and family. Finally, a strategy to improve the online media literacy of rural left-behind children is put forward.